Factors Associated With Proximal Intracranial Aneurysms to Brain Arteriovenous Malformations: A Prospective Cohort Study. Issue 6 (June 2016) - Morgan, Michael Kerin; Alsahli, Khalid; Wiedmann, Markus; Assaad, Nazih N.; Heller, Gillian Z.
Abstract : BACKGROUND: The risk of hemorrhage from a brain arteriovenous malformation (bAVM) is increased when an associated proximal intracranial aneurysm (APIA) is present. Identifying factors that are associated with APIA may influence the prediction of hemorrhage in patients with bAVM. OBJECTIVE: To identify patient- and bAVM-specific factors associated with APIA. METHODS: We analyzed a prospective database of bAVMs for factors associated with the presence of APIA. Factors analyzed included age, sex, bAVM size, aneurysm size, circulation contributing to the bAVM, location of the aneurysm, deep venous drainage, and Spetzler-Ponce categories. Multiple logistic regression was performed to identify an association with APIA. RESULTS: Of 753 cases of bAVM with complete angiographic surveillance, 67 (9%) were found to have APIA. Older age (continuous variable; odds ratio, 1.04; 95% confidence interval, 1.02-1.05) and posterior circulation supply to the bAVM (odds ratio, 2.29; 95% confidence interval, 1.32-3.99) were factors associated with increased detection of APIA. The association of posterior circulation–supplied bAVM was not due to infratentorial bAVM location because 72% of posterior circulation APIAs were supplying supratentorial bAVM. CONCLUSION: APIAs appear to develop with time, as evident from the increased age for those with APIAs. Furthermore, they were more likely present in bAVMs supplied by the posterior circulation. This may be due to a difference in hemodynamic stress. ABBREVIATIONS: APIA, associated proximal intracranial aneurysm bAVM, brain arteriovenous malformation DSA, digital subtraction angiography SMG, Spetzler-Martin grade SPC, Spetzler-Ponce category